Investigating Students' Perceptions of Digital vs. Print Reading Materials - Fenny, Tarisa; Perdhani, Widya Catherine (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
In this study, students' perceptions regarding their preference for digital or printed reading materials were analyzed using a quantitative approach. The research design employed was a survey with a descriptive design. This design aimed to collect opinions and preferences from students regarding their reading habits and experiences with both digital and print materials. A questionnaire was used to gather data from 103 students in grade 12 (science, social science, and language studies) at SMAN 10 Malang. The study showed that most students liked both printed and digital materials, but slightly preferred digital ones. They enjoyed reading digitally more than on paper because it was easier and convenient, though they felt equally comfortable with both. Students liked the appealing design of both, but digital content intrigued them more. They understood that both were important for learning English, but they favored digital materials for being up-to-date. However, they found it easier to take notes with printed materials. The study found that most students liked both digital and printed materials, but they slightly favored digital ones. The mean score for digital reading materials was 3.92, while for printed materials, it was 3.68. Overall, they did not find either format too difficult, finding digital materials quick to access but feeling neutral towards printed ones. Although students recognized the benefits of digital resources, their preference for learning from digital materials over print was neutral.